Spiritual Caregiving in Relation to Issues of Mental Health and Chaplaincy: A Case Study of Mr. K - Zhen, Ven. Guan (Journal of International Buddhist Studies, 2021)
The case study of Mr. K (pseudonym) illustrates challenges and possible interventions for individuals living with mental health issues from a spiritual caregiver perspective. Mr. K sought ordination as a lay Buddhist minister as part of a chaplaincy program. Mr. K presented with childhood abuse and neglect along with posttraumatic stress disorder (PTSD) stemming from military service. The purpose of this article is to foster open discussion on mental health issues and spiritual care through the study of Mr. K’s case. Self Psychology and Buddhist spiritual caregiving perspectives are utilized. This article proposes a theoretical Buddhist triangular healing model in which spiritual caregiving and mental health work in tandem.